With great power comes shared responsibility: Psychological power and the delegation of authority. (1st April 2017) - Haselhuhn, Michael P.; Wong, Elaine M.; Ormiston, Margaret E.
Abstract: Despite the importance of delegation as a managerial tool, we know little about how leaders' characteristics affect their decision to delegate. In this paper, we demonstrate that, holding objective markers of power constant, a psychological sense of power predicts preferences for delegation. Specifically, individuals who feel relatively powerless are less willing to delegate decision making authority compared to those who feel powerful. We find support for this pattern in two studies. These results provide insight into the factors linking power and delegation. Highlights: We know little about how leaders' characteristics affect the decision to delegate. We show that a psychological sense of power predicts the delegation of authority. Leaders who feel powerless are less willing to delegate decision making authority.